2018
DOI: 10.1007/s10147-018-1275-6
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety and depression associated with tyrosine kinase inhibitor discontinuation in patients with chronic myeloid leukemia

Abstract: Stopping TKIs outside clinical trials is feasible if the guidelines for stopping are followed and an adequate monitoring system is available. Discontinuation of TKIs requires adequate management of anxiety and depression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 25 publications
1
14
0
2
Order By: Relevance
“…There was also an increase in the reported severity of the impact of the emotional side effects of anxiety, feeling distressed and feeling upset in this phase, compared with before discontinuation of treatment. These results echo those of Sogawa et al [49], who reported significantly higher anxiety and depression on the Hospital Anxiety and Depression Scale (HADS), at reintroduction of TKI than at the point of TKI discontinuation.…”
Section: Psychological and Emotional Impact Of Tfrsupporting
confidence: 88%
“…There was also an increase in the reported severity of the impact of the emotional side effects of anxiety, feeling distressed and feeling upset in this phase, compared with before discontinuation of treatment. These results echo those of Sogawa et al [49], who reported significantly higher anxiety and depression on the Hospital Anxiety and Depression Scale (HADS), at reintroduction of TKI than at the point of TKI discontinuation.…”
Section: Psychological and Emotional Impact Of Tfrsupporting
confidence: 88%
“…As in other studies, the potential negative consequences of TKI treatment discontinuation were primarily related to emotional stress producing feelings of uncertainty, anxiety, and regret that may be brought about by treatment discontinuation or its failure [19,20,22,24,25]. Indeed, relapse and the subsequent resumption of TKI treatment have been found to increase anxiety and depression [30]. In view of the still considerable rate of relapse, these kind of concerns are also a major reason for certain patients not to discontinue TKI treatment.…”
Section: Discussionmentioning
confidence: 84%
“…However, caution is urged before adopting TFR as the sine plus ultra of CML treatment, in place of the more humble aim of at least MMR (and thus freedom from progression) without unacceptable side effects. Around 20% of otherwise eligible patients may not wish to stop treatment [16••, 56], and TKI cessation may raise levels of anxiety and depression [57]. Interestingly, a recent survey of over 1500 patients suggests that they are less concerned about TFR than haematologists, and regard other facets of the disease as of greater importance [58].…”
Section: Discussionmentioning
confidence: 99%